Pre-warning of abiotic factors in maize required for potential contamination of fusarium mycotoxins via response surface analysis. (March 2021) - Yu, Song; Jia, Bingxuan; Li, Kailin; Zhou, Haiyan; Lai, Wenshan; Tang, Yan; Yan, Zheng; Sun, Wei; Liu, Na; Yu, Dianzhen; Wu, Aibo
Abstract: Fusarium mycotoxins contaminated in maize are of serious threat to food security and safety. The main abiotic factors of mycotoxins-producing strains and circumstantial elements are crucial for mycotoxin production in the cereal matrix. In this current research work, Fusarium verticillioides and Fusarium graminearum are selected, which enable to produce the major mycotoxins in maize as common Fusarium isolates infecting maize. We first confirmed the constitution of mycotoxin profiles in 110 maize and derived feed samples collected from various provinces of China, through large-scale screening by the established high performance liquid chromatography-mass spectrometry (LC-MS/MS) approach. As indicated, the majority of mycotoxins was fumonisin, deoxynivalenol and zearalenone, frequently co-occurred with at least two kinds of mycotoxins. Interestingly, zearalenone-14-sulfate together with other masked forms of the target Fusarium mycotoxins were as co-contaminants there. Moreover, the circumstantial effects from a set of temperature and water activity (aw) are thoroughly demonstrated for potential contamination in maize flour and kernels. As revealed, the highest group factors were 0.99 and 25 °C while the relatively lower group factors were of temperature ≤20 °C or aw ≤ 0.95. Finally, a response surface analysis was performed to display the interaction of temperature-water activity interaction, required for potential contamination of Fusarium mycotoxins in maize and derived products. The risk group factors predicted by response surface equation were similar to the experimental results. This also could be valuable clues for pre-warning of mycotoxins occurrence, thus as reference data for control of mycotoxins in foods. Highlights: FBs, DON, ZEN and their masked forms co-occurred in maize and feed samples. Temperature and aw significantly affected mycotoxins production. Mycotoxins production at a lower level when temperature ≤ 20 °C or aw ≤ 0.95. Response surface analysis model can predict mycotoxins risk level and guide the storage management of maize and feed. These results provide reference data for the control of mycotoxins in food.